Considering Sound in Planning and Designing Public Spaces: A Review of Theory and Applications and a Proposed Framework for Integrating Research and Practice. (November 2016) - Bild, Edda; Coler, Matt; Pfeffer, Karin; Bertolini, Luca
We critically review the literature on the relationship between users of public spaces and their auditory environments, and how this knowledge is integrated in the planning, design, and management of public spaces as well as in technologies for acoustic and spatial data collection, analysis, and communication. To address the gaps identified in the review, we propose an activity-centered framework as a conceptual tool developed to support the integration of different types of knowledge in incorporating sound and the auditory environment in the planning and design of public spaces, by focusing on the activities that users perform in these spaces.